PROBLEM BASED LEARNING MODEL BASED ON ONLINE INTERACTIVE MULTIMEDIA TO IMPROVE UNDERSTANDING OF DANCE MOVEMENTS - AISYAH APRILIANI HIJRIYANNI; FRAHMAH SEKARNINGSIH; BEBEN BARNAS (Universitas Pendidikan Indonesia, 2024)
The focus of the problem in this research is students' weak understanding, especially understanding of dance movements, which is caused by teachers rarely using learning models during the learning process, so the learning objectives and provision of material are not optimal, resulting in learning outcomes not being by students' actual abilities. This research aims to find out the picture after implementing the online interactive multimedia-based Problem-Based Learning model. The method used by researchers in this research is an experimental method with a quantitative approach. The research design used was one group pretest and posttest. The reason this method was used was that this research only focused on one group, so the treatment given was more intense and obtained maximum results. This research was conducted at SMPN 12 Bandung with 31 students in class VII G. To find out the causal relationship between variables on dance movements after a Posttest was given to determine understanding of dance movements after being given treatment. The use of an online interactive multimedia-based Problem-Based Learning model has been proven to increase students' understanding of dance movements after research was conducted by comparing the results of students' pretest and posttest. The increase in understanding of dance movements can be seen from the difference in the average pretest and posttest scores. This is also proven by the hypothesis test carried out, the results of the t-test analysis show t-count t-table or 19.2 1.697, meaning that H1 can be accepted and H0 is rejected.